Acne and social media: A cross‐sectional study of content quality on TikTok. Issue 1 (28th November 2020) - Zheng, David X.; Ning, Anne Y.; Levoska, Melissa A.; Xiang, Laura; Wong, Christina; Scott, Jeffrey F.
Abstract: Our objective was to assess the quality of acne‐related medical information present on TikTok, the world's fastest growing social media platform. We queried the TikTok mobile application for videos tagged with "#acne" on May 1, 2020, and assessed the top 100 videos meeting inclusion criteria for content quality using DISCERN, a validated and reliable instrument for evaluating consumer health information. The mean content quality rating of videos was 2.03 (SD 0.47) which, according to the DISCERN instrument, indicates information with serious to potentially important shortcomings. Dermatologists should be aware that adolescents are using TikTok to gather acne‐related information, and should prioritize acne education in this patient demographic due to the generally low content quality of such information.